Experimental verification of a two-probe implemetration of microwave interferometry for displacement measurement - Pylypenko, O.V.; Doronin, A.V.; Gorev, N.B.; Kodzhespirova, I.F. (Технічна механіка, 2018)
This paper addresses the problem of experimental verification of a recently proposed two-probe method for displacement measurement based on microwave interferometry. The aim of this paper is to develop a technique that would allow one to verify that method by comparing the measured displacement vs. time relationship of a moving target with the actual one without recourse to complex photorecording equipment. This aim is achieved by the target being put in motion using a crank mechanism so that the actual target displacement can be calculated from the crank radius and arm length, the crank rotation period, and the crank angle at the initial time. Рассматривается задача экспериментальной проверки недавно предложенного двухзондового метода измерения перемещения на основе сверхвысокочастотной интерферометрии. Целью данной статьи является разработка методики, позволяющей провести проверку этого метода путем сравнения измеренной и фактической временной зависимости перемещения движущегося объекта без использования сложного оборудования для фоторегистрации. Данная цель достигается тем, что объект приводится в движение с помощью кривошипно-шатунного механизма, так что фактическое перемещение объекта можно рассчитать по радиусу и длине плеча кривошипа, периоду вращения кривошипа и углу поворота кривошипа в начальный момент времени. Розглядається задача експериментальної перевірки нещодавно запропонованого двозондового метода вимірювання переміщення на основі надвисокочастотної інтерферометрії. Метою цієї роботи є розробка методики, що дозволяє провести перевірку цього метода шляхом порівняння виміряної й фактичної часової залежності переміщення об’єкта, що рухається, без використання складного обладнання для фотореєстрації. Ця мета досягається тим, що об’єкт приводиться до руху за допомогою кривошипно-шатунного механізму, так що фактичне переміщення об’єкта можна розрахувати за радіусом і довжиною плеча кривошипа, періодом обертання кривошипа та кутом повороту кривошипа у початковий момент часу.